Protocol of a cluster randomised controlled trial to assess the effectiveness of a care management programme for caregivers of people with dementia (GAP study): Other innovative programs and practices. (7th December 2020) - Klein, Olga A; Kilimann, Ingo; Thyrian, Jochen René; Teipel, Stefan J; Keller, Armin; Boekholt, Melanie; Michalowsky, Bernhard; Zwingmann, Ina; Dreier‐Wolfgramm, Adina; Hoffmann, Wolfgang
Abstract: Background: About 75% of dementia care is provided by family caregivers who often experience adverse health outcomes. The identification of unmet healthcare needs of family caregivers is crucial to provide appropriate support thereby relieving the economic burden of dementia. As the first point of contact, general practitioners (GPs) have a key role in identifying burden and care needs of family caregivers. However, in routine care, this opportunity is hampered by time constraints and even if caregiver needs are being recognised, GPs often lack detailed information on regionally available support and healthcare services. Aim : To assess the clinical and cost‐effectiveness of a GP‐ and computer‐based care management programme to reduce unmet care needs of family caregivers of people with dementia (PwD). Method: This is a multi‐site, cluster randomised, controlled trial comparing a digital care management programme (intervention) with usual care (control). Five hundred family caregivers will be randomised at GP offices, specialist practices, and memory clinics, with about n =250 participants per arm. A computer‐based assessment will identify needs of family caregivers of PwD and will automatically generate an individual management plan. The treating GP will carry out the management plan generated in close collaboration with specifically qualified nurses, so‐called dementia care managers, who support and monitor the implementation of the care plan via four monthly telephone follow‐ups. All participants will receive a final follow‐up assessment at six months after randomisation. Participants in the control group will receive usual care at first and the individual management plan at the six months follow‐up. Primary outcomes are the Camberwell Assessment of Need for the Elderly and the EQ‐5D. Secondary outcomes include the Zarit Burden Interview, the Social Lubben Network Scale, and use of medical and non‐medical services. This trial is funded by the German Federal Joint Committee (G‐BA) and registered in the clinical trials database under NCT04037501. Result: We expect to obtain significant differences in primary and secondary outcomes between groups in favour of the intervention group. Conclusion: The findings of this trial will be useful in informing and improving current healthcare system structures to support family dementia caregivers within routine care practice.